Fibroblast Growth Factor Type 2 (FGF2) Administration Attenuated the Clinical Manifestations of Preeclampsia in a Murine Model Induced by L-NAME - Martinez-Fierro, Margarita L; Hernadez-Delgadillo, Gloria Patricia; Flores-Mendoza, Jose Feliciano; Alvarez-Zuñiga, Claudia Daniela; Diaz-Lozano, Martha Lizeth; Delgado-Enciso, Ivan; Romero-Diaz, Viktor Javier; Lopez-Saucedo, Adrian; Rodriguez-Sanchez, Iram Pablo; Marino-Martinez, Ivan Alberto; Garza-Veloz, Idalia (Frontiers in Pharmacology, 2021)
Background: In preeclampsia, a hypertensive disorder of pregnancy, the poor remodeling of spiral arteries leads to placental hypoperfusion and ischemia, provoking generalized maternal endothelial dysfunction and, in severe cases, death. Endothelial and placental remodeling is important for correct pregnancy evolution and is mediated by cytokines and growth factors such as fibroblast growth factor type 2 (FGF2). In this study, we evaluated the effect of human recombinant FGF2 (rhFGF2) administration in a murine model of PE induced by NG-nitro-L-arginine methyl ester (L-NAME) to test if rhFGF2 administration can lessen the clinical manifestations of PE. Methods: Pregnant rats were administrated with 0.9% of NaCl (vehicle), L-NAME (60 mg/kg), FGF2 (666.6 ng/kg), L-NAME+FGF2 or L-NAME + hydralazine (10 mg/kg) from the 10th to 19th days of gestation. Blood pressure (BP), urine protein concentrations and anthropometric values both rat and fetuses were assessed. Histological evaluation of organs from rats delivered by cesarean section was carried out using hematoxylin and eosin staining. Results: A PE-like model was established, and it included phenotypes such as maternal hypertension, proteinuria, and fetal growth delay. Compared to the groups treated with L-NAME, the L-NAME + FGF2 group was similar to vehicle: the BP remained stable and the rats did not develop enhanced proteinuria. Both the fetuses and placentas from rats treated with L-NAME + FGF2 had similar values of weight and size compared with the vehicle. Conclusion: The intravenous administration of rhFGF2 showed beneficial and hypotensive effects, reducing the clinical manifestations of PE in the evaluated model.